Identificação de Physciaceae s.l. foliosas brasileiras - Jungbluth, Patrícia [UNESP]; Marcelli, Marcelo Pinto (My University, 2012)
In the following text, characters of taxonomic importance in Brazilian foliose Physciaceae s. l. are presented and discussed.

No presente texto, são apresentadas e discutidas as características de importância taxonômica em Physciaceae s. l. foliosas que ocorrem no Brasil.
Identification of Brazilian foliose Physciaceae s.l.
Keywords: Caliciaceae; Dirinaria; Heterodermia; Hyperphyscia; Phaeophyscia; Physcia; Pyxine; Fungos liquenizados